Expression of Fas (CD95/APO-1) and Fas Ligand (FasL) in Experimentally-Induced Acute Pancreatitis. (1st April 2014) - Pardalis, Vassilios; Palli, Eleni; Lambropoulou, Maria; Tsigalou, Christina; Anagnostoulis, Stavros; Garoufalis, Grigorios; Bolanaki, Helen; Simopoulos, Constantinos; Karayiannakis, Anastasios J.
ABSTRACT Introduction: Acinar cell death is a crucial event in acute pancreatitis (AP) and may occur either by apoptosis or necrosis. The aim of this study was to investigate the expression of the apoptosis associated proteins Fas and FasL in experimentally induced severe AP. Methods: AP was induced in 30 rats by injecting 0.2 ml of 4.5% sodium taurocholate solution into the biliopancreatic duct. Sham operated animals (n = 30) and 10 normal controls were used for comparisons. Animals were killed at 6, 12, 24, 48, 72 hr and 1 week after operation (five animals at each time point) and both serum and pancreatic tissue were obtained. The severity of AP was graded by morphological evaluation and by measuring serum amylase levels. Acinar cell apoptosis was detected by the terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick-end labeling (TUNEL) assay. Tissue expressions of Fas and FasL were evaluated by immunohistochemistry. Results: Sodium taurocholate injection resulted in severe acute necrotizing pancreatitis as early as six hr after taurocholate infusion with gradually increasing severity and a peak at 72 hr, and a significant increase of serum amylase at 6 and 12 hr. Apoptotic acinar cells were observed between 48 and 72 hr. The expression of both Fas and FasL in pancreatic tissue was induced in comparison with normal controls. Fas expression in AP was higher and statistically significant at 24 hr whereas FasL expression was consistently lower with a statistical significance observed at 12 hr when compared to sham-operated animals suggesting Fas upregulation and FasL downregulation in this model of AP. Conclusions: Induction and sequential changes in the expressions of Fas and FasL occur during taurocholate induced severe AP in rats and their temporal modulation might associate with acinar cell death by apoptosis.